Peripheral blood blast clearance is an independent prognostic factor for survival and response to acute myeloid leukemia induction chemotherapy. Issue 12 (29th August 2016) - Short, Nicholas J.; Benton, Christopher B.; Chen, Hsiang‐Chun; Qiu, Peng; Gu, Lisa; Pierce, Sherry; Brandt, Mark; Maiti, Abhishek; Min, Taejin L.; Naqvi, Kiran; Quintas‐Cardama, Alfonso; Konopleva, Marina; et al.
Abstract : In patients with acute myeloid leukemia (AML), rapid reduction of circulating blasts with induction chemotherapy may serve as an in vivo marker of chemosensitivity. We performed a retrospective analysis of 363 patients with untreated AML who received induction chemotherapy in order to determine the relationship between day of blast disappearance (DOBD) and complete remission (CR) rates, event‐free survival (EFS), and overall survival (OS). DOBD ≤ 5 vs. >5 was identified as the most discriminating cutoff for OS. DOBD > 5 was observed in 35 patients (9.6%). The CR rate for patients with DOBD ≤ 5 vs. >5 was 74.0 and 28.6%, median EFS was 9.4 and 1.8 months, and median OS was 17.1 and 5.8 months, respectively ( P < 0.001 for all). DOBD > 5 was independently associated with a lower CR rate and shorter EFS and OS ( P < 0.001 for all). DOBD > 5 retained prognostic significance for EFS and OS when patients were stratified by cytogenetic risk group, de novo vs. secondary or therapy‐related AML, European LeukemiaNet‐based risk groups, and whether CR was achieved. We propose DOBD > 5 as a simple and early marker of disease resistance that identifies patients with poor prognosis who otherwise may not be identified with existing risk stratification systems. Am. J. Hematol. 91:1221–1226, 2016. © 2016 Wiley Periodicals, Inc.